Sales Concentration Index in the Iranian Car Market - Kazemzadeh, Emad; Sheikh Zeinoddin, Azar (Industrija, 2015)
Concentration is among the key indicators of market structure. The number of manufacturers and distribution of market between firms with different sizes can be examined using concentration index. In this paper, the concentration ratio, Herfindahl-Hirschman Index, Hall-Tiedman Index, comprehensive industrial concentration index, entropy and Hannah-Kay index were used during 1996, 2011, 2006 and 2011. The main objective of the present study is to measure concentration in the Iranian car market and show its changes during 1996-2011. The results indicated a high concentration in the Iranian automotive industry. Even with the advent of new firms to the Iranian automotive industry and increased total production, there has been a constant concentration in the automotive industry.